Narrative medicine in metastatic prostate cancer reveals ways to improve patient awareness & quality of care. (15th June 2018) - De Vincentis, Giuseppe; Monari, Fabio; Baldari, Sergio; Salgarello, Matteo; Frantellizzi, Viviana; Salvi, Elisabetta; Reale, Luigi; Napolitano, Silvia; Conti, Giario; Cortesi, Enrico
Aim: To describe the journey of patients with metastatic castration-resistant prostate cancer (mCRPC) in treatment with radium-223.Methods: A multiperspective analysis was performed using narrative medicine in four Italian centers.Results: The substantial impact of mCRPC on quality of life through all phases of the disease was described. After an initial lack of awareness of the disease or denial of its effects, symptoms of pain, fatigue and side effects often led to sadness, fear and loneliness. The majority underwent radium-223 therapy positively, restoring their quality of life and routine activities.Conclusion: Using narrative medicine, the importance of a patient-centered approach in the pathway of care for patients with mCRPC through all the stages of the disease was highlighted.